Synthesis and Characterization of Composite Nanoparticles for Imaging - Magdalene Paul, Amy (Asian Journal of Chemistry, 2013)
Dual functions of magnetic and fluorescent properties were created in composite particles that incorporated magnetite (Fe3O4) nanoparticles (MNPs) as particle cores and fluorescent pyrene in particle shells of poly lactate-co-glycolide (PLGA). The Fe3O4 nanoparticles were prepared by co-precipitation method and surface modified with oleic acid. MNPs were prepared by co-precipitating iron(II) and iron(III) in alkaline solution and then treating under hydrothermal conditions. Surface modification of magnetic nanoparticles by organic surfactants is known to provide them with solubility in organic solvents. The structural, magnetic and adsorption properties of iron oxide nanoparticles are derived in the presence of oleic acid as the capping agents. The surfactants provide them with excellent stability and solubility in organic solvents like toluene or chloroform. The presence of capping agents or high reaction temperatures favours the formation of smaller nanoparticles. The adsorption of the surfactants (chemisorption) was identified with FT-IR spectroscopy.Then, the magnetite particles were coated with the pyrene/ PLGA by emulsion-diffusion method. The composite particles prepared had both magnetic and fluorescent properties. The present work proposes a method for synthesizing the dually functional particles, which have a core-shell structure. The particles in this work consist of an inner core of Fe3O4 nanoparticles and a hybrid shell of polymer and organic dye. A basic technique of this work is polymer coating on Fe3O4 nanoparticles. The prepared nanoparticles were characterized by scanning electron microscopy, particle size analyzer, X-ray diffraction, Gauss meter, Fourier transform infrared spectroscopy and fluorescence spectroscopy. The nanoparticles could generate singlet oxygen to cause remarkable photodynamic antitumor effects. These suggest that composite nanoparticles have great potential in diagnostic magnetic resonance imaging.